Unexpected Rotamerism at the Origin of a Chessboard Supramolecular Assembly of Ruthenium Phthalocyanine. Issue 64 (2nd November 2017) - Mattioli, Giuseppe; Larciprete, Rosanna; Alippi, Paola; Bonapasta, Aldo Amore; Filippone, Francesco; Lacovig, Paolo; Lizzit, Silvano; Paoletti, Anna Maria; Pennesi, Giovanna; Ronci, Fabio; Zanotti, Gloria; Colonna, Stefano
Abstract: We have investigated the formation and the properties of ultrathin films of ruthenium phthalocyanine (RuPc)2 vacuum deposited on graphite by scanning tunneling microscopy and synchrotron photoemission spectroscopy measurements, interpreted in close conjunction with ab initio simulations. Thanks to its unique dimeric structure connected by a direct Ru−Ru bond, (RuPc)2 can be found in two stable rotameric forms separated by a low‐energy barrier. Such isomerism leads to a peculiar organization of the molecules in flat, horizontal layers on the graphite surface, characterized by a chessboard‐like alternation of the two rotamers. Moreover, the molecules are vertically connected to form π‐stacked columnar pillars of akin rotamers, compatible with the high conductivity measured in (RuPc)2 powders. Such features yield an unprecedented supramolecular assembly of phthalocyanine films, which could open interesting perspectives toward the realization of new architectures of organic electronic devices. Abstract : An unexpected chessboard ‐like pattern appears in ultrathin films of ruthenium phthalocyanine deposited on graphite. The comparison between STM and PES measurements, interpreted in close conjunction with DFT simulations, unveils the properties of a peculiar supramolecular assembly: two stable isomers concur in the formation of the organic film, driven by strong non‐covalent intermolecular interactions that act within a single molecular layer and are extended to the assembly of multilayered structures.